Partnering with students to redesign an introductory chemistry laboratory course: An exploration of the process and implications - Jardine, Hannah Elizabeth; Frome, Gavin; Campbell Griffith, Elizabeth (International Journal for Students as Partners, 2023)
The most effective teaching and learning environments are those in which students are involved as active partners with faculty, and the greatest impact occurs when faculty go beyond asking students for feedback and instead involve them in design, production, and implementation. In this paper, we explore the process of student-faculty co-creation by presenting a specific case involving students as partners in the redesign of an introductory chemistry laboratory course to incorporate more group learning, support students’ skill development, and increase students’ sense of belonging in chemistry. This case study investigates how faculty can set up and structure a successful co-design partnership and attend to potential challenges as well as how educational developers and teaching centers can work in partnership with faculty and students to design or redesign courses.